Acute and subchronic oral toxicity studies of Nelumbo nucifera stamens extract in rats - Kunanusorn P. (2017)
Ethnopharmacological relevance: Since the use of Nelumbo nucifera stamens in herbal medicines as well as in cosmetic products are highly prevalent in Thailand and increasing worldwide, acute and subchronic toxicity studies to confirm the safe use of Nelumbo nucifera stamens are warranted. Aim of the study: Acute and subchronic oral toxicity studies of Nelumbo nucifera stamens extract in rats were performed in the present study in order to evaluate its safety. Materials and methods: In acute toxicity study, Nelumbo nucifera stamens extract was administered by oral gavage to Sprague-Dawley rats (5 males and 5 females) at a dose of 5000 mg/kg. In subchronic toxicity study, the extract at doses of 50, 100, and 200 mg/kg/day were given orally to groups of rats (6 rats/dose/sex) for 90 consecutive days. Results: The extract at a dose of 5000 mg/kg produced no treatment-related signs of toxicity or mortality in any of the animals tested during 14 days of the study. In the repeated dose 90-day oral toxicity study, there was no significant difference in body weight between the control and all treatment groups with the exception of the body weight of the female group treated with 200 mg/kg/day of the extract which was statistically significantly less than that of its control counterpart on day 90 but the percent weight changes of both groups were almost similar. Some statistically significant differences in hematological and biochemical parameters as well as in some internal organ weights of both male and female rats treated with the extract at the highest dose were observed. However, no abnormality of internal organs was observed in both gross and histopathological examinations. Conclusions: These results suggest that the oral lethal dose of Nelumbo nucifera stamens extract for male and female rats is in excess of 5000 mg/kg and the no-observed-adverse-effect level (NOAEL) of the extract for both male and female rats is considered to be 200 mg/kg/day. © 2011 Elsevier Ireland Ltd.